3
$\begingroup$

How to derive the following formula:

where $\sigma(y)$ is the standard deviation of $y$ (dependent variable), and $\rho(x,y)^2$ is correlation between $x$ and $y$ squared, $\sigma(\epsilon)$ the standard deviation of the error.

$$ \sigma(\epsilon) = \sigma(y) \sqrt{1-\rho(x,y)^2} $$

if $y = a +bx + \epsilon$.

$\endgroup$
3
  • 1
    $\begingroup$ The answer at stats.stackexchange.com/a/1448 includes an illustration showing this result is merely the Pythagorean Theorem. $\endgroup$ – whuber Aug 30 '13 at 21:46
  • $\begingroup$ This reads like a standard textbook question. In what context does this question arise (i.e. what are you doing that it would lead you to ask this?) $\endgroup$ – Glen_b Aug 31 '13 at 0:14
  • $\begingroup$ Thank you so much everyone this really helped me out (to Comp_Warrior for editing it and for those who answered). This was a question in the lecture notes I had and I tried for about an hour to get it but because the textbook I use focuses more on the estimates and not true value of a regression I was getting confused. Thanks again. $\endgroup$ – Mauro Augusto Aug 31 '13 at 10:36
2
$\begingroup$

Since $X$ and $\epsilon$ are supposed to be independent and so uncorrelated, you can subtract the means, square and average to give $\sigma^2_Y = b^2 \sigma^2_X + \sigma^2_\epsilon$.

But $b^2 \sigma^2_X = \rho_{X,Y}^2 \sigma^2_Y$ so you can substitute and rearrange to get your result.

$\endgroup$
1
$\begingroup$

And here is a really explicit derivation:

For simplicity assume that $a=0$ and that your data is mean adjusted: $E[x]=0; E[y]=0$:

$$\epsilon=y-\beta x$$ $$E[\epsilon]=E[y]-E[x]\beta=0$$

So you get the formula for the variance of $\epsilon$: $$Var[\epsilon]=E[(y-\beta x)^2]$$ $$=E[y^2-2y\beta x+\beta^2 x^2]$$ $$=E[y^2]-2\beta E[xy]+\beta^2E[x^2]$$ $$=\sigma_y^2-2\beta \sigma_{xy}+\beta^2 \sigma_x^2$$

And about the slope coefficient $\beta$ you know: $$\beta=\frac{\sigma_{xy}}{\sigma_x^2}$$ Then insert this in the last formula: $$Var[\epsilon]=\sigma_y^2-2\frac{\sigma_{xy}}{\sigma_x^2}\sigma_{xy}+\frac{\sigma_{xy}^2}{\sigma_x^2 \sigma_x^2}\sigma_x^2$$

Then expand the last two terms with $\frac{\sigma_y^2}{\sigma_y^2}$ to get: $$Var[\epsilon]=\sigma_y^2-2\frac{\sigma_{xy}^2}{\sigma_x^2} \frac{\sigma_y^2}{\sigma_y^2}+\frac{\sigma_{xy}^2}{\sigma_x^2 \sigma_x^2}\sigma_x^2 \frac{\sigma_y^2}{\sigma_y^2}$$ $$=\sigma_y^2-2\rho_{xy}^2\sigma_y^2+\rho_{xy}^2\sigma_y^2$$ $$=\sigma_y^2-\rho_{xy}^2\sigma_y^2=\sigma_y^2(1-\rho_{xy}^2)$$

And finally: $$\sqrt{Var[\epsilon]}=\sigma_\epsilon=\sigma_y\sqrt{(1-\rho_{xy}^2)}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.